DAMPAK OJEK ONLINE TERHADAP PENDAPATAN OJEK PANGKALAN DITINJAU DALAM PERSPEKTIF ISLAM (Studi Ojek Pangkalan Kelurahan Beliung Indah) - Hikmah Puspita Sari; Ahmad Syahrizal; Saijun Saijun (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the impact of the existence of online motorcycle taxis on the income of base motorcycle taxis in Beliung Village. This research is of a qualitative type. The object of this research is motorcycle taxi drivers at the base of Beliung Indah Village. The data sources used are primary data and secondary data. By carrying out data analysis methods, namely observation, interviews and personal documentation, then the data is processed using data processing techniques. The research results show that: The existence of online motorcycle taxis has a negative impact on the income level of base motorcycle taxi drivers. There was a decrease in income levels expressed by motorbike taxi drivers in Banjarbaru City between before and after the existence of online motorbike taxis. The average income earned by motorbike taxi drivers before the existence of online motorbike taxis was around Rp. 50,000.00 – IDR 100,000.00 thousand per day and after online motorbike taxis are only around IDR 30,000.00 – IDR 40,000.00 thousand per day and sometimes you don't even get anything at all.